2015
DOI: 10.5897/ajmm2015.0475
|View full text |Cite
|
Sign up to set email alerts
|

A review and analysis of the role of integrated marketing communication message typology in the development of communication strategies

Abstract: This conceptual paper proposes that communication strategies should be aligned to the IMC message typology in its entirety. In order to shed light on the role of IMC in the development of communication strategies a literature review was conducted. The literature review revealed that IMC is a logical structure of developing communication strategies. An organisation should control (planned) or influence messages (unplanned, product, service) to ensure message consistency and maximum communication impact. In simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…According to Baloyi (2019), TVET College open day activities, advertisements on radio and television stations as well as college publications such as catalogues and brochures have a significant impact on students' decisions to enrol at TVET colleges because they give students access to information about academic resources, student support service options, college qualification aspirations, continuous enrolment options, college experiences, and financial aids that are more important in predicting students' eventual completion of college. The study by Mudzanani's (2018) which analysed the integrated marketing communication message typology at a TVET college, concluded that the college had the challenge of raising awareness of its news value in the media. This finding by Mudzanani confirms the lack of visibility of TVET colleges which can lead to the misconceptions about TVET colleges as shown by the findings of the present study.…”
Section: Expectations Of Tvet Collegesmentioning
confidence: 99%
“…According to Baloyi (2019), TVET College open day activities, advertisements on radio and television stations as well as college publications such as catalogues and brochures have a significant impact on students' decisions to enrol at TVET colleges because they give students access to information about academic resources, student support service options, college qualification aspirations, continuous enrolment options, college experiences, and financial aids that are more important in predicting students' eventual completion of college. The study by Mudzanani's (2018) which analysed the integrated marketing communication message typology at a TVET college, concluded that the college had the challenge of raising awareness of its news value in the media. This finding by Mudzanani confirms the lack of visibility of TVET colleges which can lead to the misconceptions about TVET colleges as shown by the findings of the present study.…”
Section: Expectations Of Tvet Collegesmentioning
confidence: 99%
“…This implies that the organisation must communicate the same messages through all its promotional mixes and coordinate all its communication in order to maintain synergy, consistency and continuity with its various publics. Porcu, Carcia and Kitchen (2011:326) study conducted by Mudzanani (2015) revealed that communication objectives should not only be linked to planned product (marketing communication) tools, but the objectives should also be aligned to the unplanned, product and service messages. While, a study conducted by Dapi (2012) found that there is a strong relationship between integrated marketing communication and brand equity as effective IMC programme will leads to brand equity.…”
Section: Integrated Marketing Communicationmentioning
confidence: 99%
“…Bajo esta óptica, la Teoría de las Comunicaciones Integradas del Marketing (CIM) ha definido a la consistencia de marca como la unidad creativa y visual que debería existir entre la identidad de marca y las piezas de comunicación (Tafesse, 2015). Las organizaciones pueden mantener la consistencia de marca cuando incluyen elementos alusivos a su identidad visual y creativa en anuncios publicitarios; es decir, mensajes consistentes con la personalidad de marca que contribuyan a eliminar posibles contradicciones (Brasel, 2012;Mudzanani, 2015). De este modo, la consistencia de la marca se evidencia en términos de si las publicaciones hacen uso del nombre de la marca, el logotipo, el eslogan, los colores y la aparición del producto (Tafesse, 2015).…”
Section: Consistencia De Marcaunclassified